Why railways fail: Colonial railways and economic development in Habsburg Bosnia-Herzegovina - Magnus Neubert; Stefan Nikolić (European Historical Economics Society (EHES), 2025)
Are railways always a harbinger of prosperity? We examine the economic effects of railways in Bosnia-Herzegovina under Habsburg colonial rule. Our novel dataset consistently tracks the non-agrarian population share of over 4,500 settlements in Habsburg Bosnia in 1885, 1895, and 1910, based on census records. Applying the inconsequential units approach, with least cost paths as our instrumental variable, we estimate the effect of railway access on structural transformation. Normal-gauge railways deindustrialized Bosnian settlements by exposing local crafts to imperial competition. Narrow-gauge railways accelerated structural transformation temporarily, primarily by attracting foreigners. Narrow-gauge railways had a more sustained impact on structural transformation in settlements endowed with human capital and secured by law enforcement. Our findings suggest colonial railways are no silver bullet for economic development; transport infrastructure requires development prerequisites to have a lasting positive effect.
Keywords: I25; J21; N94; O18; R11; 330; railways; occupational structure; Bosnia-Herzegovina; Habsburg Empire